Netizen's Perception of Jember Tourism Attraction in Info Warga Jember Official Group Facebook Platform - Mushthofa Kamal; Degita Danur Suharsono (English and Tourism Studies, 2023)
The aim of this research is to identify the perceptions of Facebook users who are affiliated with the Info Warga Jember Official (IWJ) group related to the condition of tourism attractions in Jember Regency in 2022-2023. This research uses a qualitative descriptive approach. The results of this study obtained that public perceptions of tourism attractions in Jember Regency are considered to still need improvement efforts related to adjusting entrance ticket rates and parking rates, as well as managing tourist areas. In addition, perceptions related to new tourism attractions in Jember Regency need to be equipped with complete and clear information. Keywords: social media, perception, tourism attraction